Effect of Rumensin on performance of growing heifers - Bolsen, K.; Corah, L.; Fink, G.; Riley, Jack G. (Kansas State University. Agricultural Experiment Station, 2011)
We used 136 Hereford heifer calves in two studies to determine the effect on performance of 200 mg monensin (trade name Rumensin) per head daily. It significantly improved gain by 7.5% and 4.6% in trials 1 and 2 respectively, and significantly improved efficiency 11.6% and 12.2%, respectively.
1776-1976 "Buffalo to Beef" is known as Cattlemen’s Day, 1976
Keywords: Beef; Rumensin; Performance; Heifers